Vampire War Trilogy - Darren Shan (London, United Kingdom HarperCollins Publishers, 2005)
The nightmare continues...Vampire War Trilogy comprising: Hunters of the Dusk, Allies of the Night and Killers of the Dawn. Join Darren Shan's descent into the darkness. HUNTERS OF THE DUSK Darren Shan leaves Vampire Mountain on a life or death mission. Darren scours the world in search of the Vampaneze Lord, bu the road ahead is lined with the bodies of the damned. ALLIES OF THE NIGHT Darren Shan faces his worst nightmare yet - school! But bodies are piling up and the past is catching up with the hunters fast! KILLERS OF THE DAWN Darren Shan becomes public enemy Number One. As the vampires prepare for deadly confrontation, is this the end for Darren and his allies?
Keywords: Science Fiction -- Science Fiction; Fantasy -- Fantasy